Improve Creativity of Early Children Age with Art Activities - Anggraini, Lilia; Yuwono, Haryono (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
Improving the ability of children's creativity needs to be improved to find out how to develop children's creativity through art activities. art is very important and very influential in the process of growth and development of early childhood in various aspects. Early childhood will more easily accept the fun learning process, with learning and dominating the child. With various art activities that provide opportunities for children so that children can develop their creativity through art activities such as visual arts and performance art consisting of pictures, paintings, collages, clay, wood, playdough, songs, the combination of movements, musical instrument play, drama and many more, to develop creativity lift the talents and potential possessed by early childhood. So that children can freely express themselves to foster children's creativity to create something new that will further develop. This study uses qualitative research with the literature review method.